Factors affecting knowledge retention of anatomical concepts among medical students - Reyes, Julius Ceazar H. MD
Purpose: Knowledge learned in Anatomy is often quickly forgotten. This study aims to investigate the level of knowledge and factors affecting loss post-instruction. Methods: This is a prospective cohort conducted among first-year medical who underwent neuroanatomy module and later followed-up after 5 months using a 32- item test-retest. Items were categorized as to question format, instructional delivery and provision for feedback. Students were randomized to receive a post-test given immediately after instruction and during the retention interval, they were randomized to take series of test-retest spaced in 4 weeks interval. Knowledge loss was determined using the computed Knowledge Loss Percentage (KLP). Results: A total of 225 students completed the study. There was a 15.65% overall loss noted at the end of 5 months. Basic knowledge, mcq question and traditional lecture demonstrated the highest computed KLP when compared with their counterpart variables. Feedback, was noted to decrease the impact of knowledge loss (KLP=9.34) as compared to items not provided with feedback (KLP=20.51). Immediate testing showed a non-significant difference compared to those who did not receive any test at all (p>0.825). Repeated testing demonstrates a 4-fold increase in overall recall on learned concept (KLP=4.34) compared to those administered with a single test only (KLP=26.73) Conclusion: Knowledge loss occurs after knowledge is gained post and more pronounced among basic concepts. Clinical correlation, MCQ, feedback, and frequent testing, can lessen the impact of knowledge loss. Clinical correlates-traditional lecture-MCQ, has the most significant retention capability. Equally, basic knowledge-flipped classroom-MCQ can offer significant retention. Immediate testing does not affect retention. Recommendation: To reduce the effect of knowledge loss, this study recommends that multiple testing, appropriate matching of knowledge level with strategies be employed to decrease the impact of knowledge loss. Use of MCQ, frequent testing, and feedback should be the mainstay in planning assessment.